Hubungan Pengetahuan Life Style Pada Lansia dengan Penyakit Hipertensi di Posyandu Anggrek Bulan Negeri Rutong, Wilayah Kerja Puskeamas Rawat Inap Hutumuri, Kecamatan Leitimur Selatan. - Thirza lessy; Ernawati Hatuwe; FadlyKaliky; Yerry Soumokil (Pusat Riset dan Inovasi Nasional, 2024)
Hypertension is a problem that needs to be watched out for, because there are no specific signs and symptoms of hypertension and some people still feel healthy to do activities as usual. This is what makes hypertension a silent killer, people will realize they have hypertension when the symptoms they feel get worse and check themselves to health services (Purwono et al., 2020). Purpose: This study aims to determine the Relationship between Lifestyle Knowledge in the Elderly and Hypertension at the Anggrek Bulan Negeri Rutong Elderly Posyandu, Hutumuri Inpatient Health Center Work Area, South Leitimur District. Method: The research design used in this study was Quantitative with a correlational method. Results: There was a relationship between Lifestyle knowledge in the elderly and hypertension (ρ-value = 0.000). Conclusion: There is a relationship between Lifestyle and hypertension in the elderly at the Anggrek Bulan Negeri Rutong Posyandu, Leitimur District